Avaliação de blendas de hidrocolóides na estabilização do néctar de caju: aspectos reológicos e sensoriais - Lemos, Tatiana de Oliveira (2012)
One of the biggest issues in the production of cashew nectar is to ensure the stability of the dispersion since the phase separation depreciates the visual appearance and alters its viscosity which can compromise the sensory quality and therefore its competitiveness in the market Thus this study was aimed at obtaining a blend of hydrocolloids that was effective in physical stabilization and maintenance of intrinsic characteristics of cashew nectar The study was conducted in three steps: characterization of the commercial cashew nectars (trademarks A B C and D) production and characterization of cashew nectars in laboratory and industrial scale In the first step the analysis showed that the commercial cashew nectars were within the range of electrostatic instability (where the nectar A was the most stable) and according to the Standard of Identity and Quality (PIQ) provided for Brazilian law except for the pulp content of the A C and D nectars The D nectar showed greater physical stability when compared to others ones All nectars exhibited non-Newtonian behavior with pseudoplastic characteristics The A and B nectars showed good sensory acceptance In the next step it was used guar/xantan guar/gellan and guar/kappa-carrageenan blends and was applied the experimental planning factorial orthogonal of first order and sensory tests to select the blend of hydrocolloids to be used for production of cashew nectar in industrial scale At this step the nectar containing the blend of guar/kappa-carrageenan (0.5% w/w) was chosen for showing good results on the physical stability viscosity and sensory acceptance tests The selected blend was used to produce 1000 L of cashew nectar aseptically packaged in Tetra Brik packages of 1 L and subjected to physicochemical physical rheological and sensory analysis The industrial nectar was found according to the PIQ in the range of incipient instability and higher fiber content than the commercial ones It also showed good physical stability which can be attributable to the steric stabilization mechanism provided by the blend of hydrocolloids and non-Newtonian and pseudoplastic behavior The sensory tests showed good acceptance for the color homogeneity aroma body and overall impression attributes and with a few adjustments in the formulation it could be marketed and possibly to compete with some brands already on the market of nectars